Comparison of Performance between Organic Farming and Traditional Farming of Freshwater Prawn in Respect of Production and Economics (Journal of Environmental Science and Natural Resources, 2016)
An experiment was conducted to compare the performance between traditional farming and organic farming of freshwater prawn in respect of production and economics. The experiment had two treatments, namely: Traditional (TT) and Organic (TO) with same stocking density (20000 juveniles ha-1) in triplicate. In treatment TO, formulated feed with locally available ingredients were used, and maize flour and bamboo branches were provided for maintaining C:N ratio to 20 and for developing periphyton, respectively. In treatment TT, only commercially available prawn feed was applied. No fertilizers or other types of chemicals or antibiotics were used in both treatments. There were no significant differences (P?0.05) of different water quality parameters between both treatments. Weight gain and specific growth rate (% body weight day-1) of prawn was significantly higher (P